Childhood and Adulthood Passive Smoking and Nonalcoholic Fatty Liver in Midlife: A 31-year Cohort Study - Wu Feitong; Pahkala Katja; Juonala Markus; Jaakkola Johanna; Rovio Suvi P; Lehtimäki Terho; Sabin Matthew A; Jula Antti; Hutri-Kähonen Nina; Laitinen Tomi; Viikari Jorma SA; Magnussen Costan G; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2022)
INTRODUCTION: Identifying early life risk factors remains key to the prevention of nonalcoholic fatty liver (hereinafter "fatty liver") in adulthood. However, the longitudinal association of childhood passive smoking with adult fatty liver is not studied. We examined the association of childhood and adulthood passive smoking with fatty liver in midlife.METHODS: This was a 31-year prospective cohort study of 1,315 participants. Information on childhood passive smoking (parental smoking) was collected in 1980 (aged 3-18 years) and 1983 and adulthood passive smoking in 2001, 2007, and 2011. Fatty liver was determined by ultrasound in 2011 (aged 34-49 years).RESULTS. The prevalence of fatty liver was 16.3%. Both childhood and adulthood passive smoking were associated with higher risk of fatty liver, adjusting for potential confounders such as age, sex, childhood socioeconomic status, and adulthood physical activity and alcohol consumption (relative risk = 1.41, 95% confidence interval: 1.01-1.97 for childhood; 1.35, 1.01-1.82 for adulthood). Individuals with persistent exposure to passive smoking between childhood and adulthood had the highest risk (relative risk = 1.99, 95% confidence interval: 1.14-3.45) compared with those without passive smoking in either childhood or adulthood.DISCUSSION: Passive smoking in both child and adult lives are associated with increased risk of adult fatty liver, suggesting that the prevention of passive smoking should start as early as possible and maintain throughout lifetime.